2019
DOI: 10.1371/journal.pone.0226716
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, procrastination, and burnout in post-secondary faculty: An international longitudinal analysis

Abstract: To address the present research gap on relations between motivational beliefs, self-regulation failure, and psychological health in post-secondary faculty, the present study used associative latent growth modeling to longitudinally examine relationships between self-efficacy, procrastination, and burnout (emotional exhaustion) in faculty internationally. Findings from 3,071 faculty participants (70% female, 69 countries) over three time points (5–6 month lags) showed greater self-efficacy at baseline to corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 94 publications
6
27
0
1
Order By: Relevance
“…A research article associated self-efficacy with passive and active procrastination (Hicks & Storey, 2015). Another article showed the relationship between procrastination and burnout (Hall et al, 2019). Procrastination relates also to personal aspects of life like the study of Ferrari and Landreth (Ferrari & Landreth, 2014), wherein the exposed rural procrastinators narrate life challenges in their home, family lives, and in their work settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A research article associated self-efficacy with passive and active procrastination (Hicks & Storey, 2015). Another article showed the relationship between procrastination and burnout (Hall et al, 2019). Procrastination relates also to personal aspects of life like the study of Ferrari and Landreth (Ferrari & Landreth, 2014), wherein the exposed rural procrastinators narrate life challenges in their home, family lives, and in their work settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the research, Austin and Gamson (1983) argue that faculty are both intrinsically motivated (e.g., personally meaningful and rewarding work) and extrinsically motivated (e.g., through tenure and promotion standards). Additionally, motivation within the learning context has been studied in many forms including the role of self-efficacy in procrastination and burnout (Hall, Lee, & Rahimi, 2019), the role of structure and agency in the intrinsic motivation to be good teachers (Leibowitz, Schalkwyk, Ruiters, Farmer, & Adendorff, 2012), and the ways in which faculty are motivated to prioritize research over teaching (Pesce, 2015). Motivation can play a key role in sustainable academic programming and development; however, the perceptions of faculty and administration may vary in effective motivational strategies (Blašková, Majchrzak-Lepczyk, Hriníková, & Blaško, 2019).…”
Section: Motivationmentioning
confidence: 99%
“…For example, recent research found teaching self-efficacy was a greater predictor of job satisfaction in faculty than research self-efficacy (Ismayilova & Klassen, 2019). Through exploring faculty expectations beyond self-efficacy, connections to faculty development may lead to longer job satisfaction as a teacher-scholar-reducing burn-out (Hall et al 2019).…”
Section: Expectationsmentioning
confidence: 99%
See 2 more Smart Citations